Leaf Phosphorus Concentration Regulates the Development of Cluster Roots and Exudation of Carboxylates in Macadamia integrifolia - Zhao, Xin; Lyu, Yang; Jin, Kemo; Lambers, Hans; Shen, Jianbo (Frontiers in Plant Science, 2021)
Phosphorus (P) deficiency induces cluster-root formation and carboxylate exudation in most Proteaceae. However, how external P supply regulates these root traits in Macadamia integrifolia remains unclear. Macadamia plants were grown hydroponically with seven P levels to characterize biomass allocation, cluster-root development and exudation of carboxylates and acid phosphatases. Plant biomass increased with increasing P supply, peaking at 5 μM P, was the same at 5-25 μM P, and declined at 50-100 μM P. Leaf P concentration increased with increasing P supply, but shoot biomass was positively correlated with leaf P concentration up to 0.7-0.8 mg P g-1 dry weight (DW), and declined with further increasing leaf P concentration. The number of cluster roots declined with increasing P supply, with a critical value of leaf P concentration at 0.7-0.8 mg P g-1 DW. We found a similar trend for carboxylate release, with a critical value of leaf P concentration at 0.5 mg g-1 DW, but the activity of acid phosphatases showed a gradually-decreasing trend with increasing P supply. Our results suggest that leaf P concentration regulates the development and functioning of cluster roots, with a critical P concentration of 0.5-0.8 mg g-1, above which macadamia growth is inhibited.